Ecuador : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Ecuador. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that since the fourth quarter of 2014, the economy of Ecuador has been hit by external shocks and is slowing down. The sharp decline in the international oil price, by about half for the Ecuadorian mix, significantly undercut oil revenues. In addition, competitiveness is being eroded by the real appreciation of the exchange rate. In the face of the economic slowdown, bank liquidity conditions have tightened, credit growth has slowed, and nonperforming loans have risen. Despite the slowdown, inflation is picking up. Owing to the shocks and expected adjustment, the economy is projected to contract somewhat in 2015, while the external position deteriorates.